Surgical Reconstruction of Mitral Restenosis Complicated by a Critically Small Left Ventricular Cavity and Giant Left and Right Atriomegaly (Clinical Case) - Volodymyr V. Popov; Oleksandr O. Bolshak; Valery Zh. Boukarim; Olena V. Khoroshkovata; Oleksii M. Gurtovenko; Kateryna V. Pukas (Український журнал серцево-судинної хірургії, 2023)
Background. Comprehensive reconstruction of the left and right parts of the heart in giant left atriomegaly, adequate tactics of mitral valve replacement in case of concomitant tricuspid insufficiency and dilation of the right atrium lead to an improvement in the functional state of the myocardium as early as at the hospital stage.